Analisis Kemampuan Literasi Numerasi Matematis ditinjau dari Self Confidence - Aprilione, Sagita; Simatupang, Gugun Manosor; Huda, Nizlel (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2025)
This study aims to describe and analyze students' mathematical literacy skills in terms of self-confidence in the material of arithmetic sequences and series. This research was conducted at SMAN 4 Jambi City, class Phase E1, academic year 2024/2025. This type of research is qualitative research. The subjects of this study were 6 people consisting of 2 students with each category, namely high, medium, and low. The instruments in this study were in the form of a self-confidence questionnaire, a numeracy literacy ability test sheet and an interview guideline sheet. Based on the results of the questionnaire and test questions on mathematical numeracy literacy skills in terms of self-confidence in the material of arithmetic sequences and series. This study shows that students with a high level of self-confidence have good mathematical numeracy literacy skills by meeting all indicators. While students with a moderate level of self-confidence have fairly good mathematical numeracy literacy skills. The first moderate self-confidence student was able to meet two indicators of mathematical numeracy literacy skills while the second moderate self-confidence student only met one indicator of mathematical numeracy literacy skills. Then, low self-confidence students are less able to fulfill mathematical numeracy literacy skills. The first low self-confidence student only fulfills two indicators of mathematical numeracy literacy skills. The second low self-confidence student only fulfills one indicator of mathematical numeracy literacy skills.